An introduction to Masjid Jamek Sultan Abdul Samad: yesterday, today and tomorrow - Abdul Rahim, Asiah; Mohammad Aqif, Megat; Azmatun, Maizan; Aripin, Srazali; Nafisa, Nurain, (KAED Universal Design Unit (KUDU), and Department of Architecture, Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2022)
This chapter provides an overview of Masjid Jamek Sultan Abdul Samad that covers its location, site context, and evolution of the Masjid before going further focusing onto the Masjid itself. The significant aspect that comes with Masjid Jamek Sultan Abdul Samad is relating to the history of Kuala Lumpur and includes other aspects from social, cultural, and aesthetic. Measured drawings are also a part of the focus field in the heritage studies and for this specifically, Masjid to show its’ development throughout the years.